Kosztolányi és a Nyugat Barátok Köre - Buda, Attila (Studia Litteraria, 2018)
From the beginning of 1931, the editors of an important journal of Hungarian literature called Nyugat (West) organized a series of lectures, under the title “West Friends Circle”. Their aim was to organize a reading audience connected to the journal with the help of regular these occasions. The authors of the nyugat also performed on the lectures, with Dezső Kosztolányi making several appearances. The study examines the contents of his lectures, using his writings with similar titles.